2021
DOI: 10.33321/cdi.2021.45.5
|View full text |Cite
|
Sign up to set email alerts
|

Decreased incidence of enterovirus and norovirus infections during the COVID-19 pandemic, Victoria, Australia, 2020

Abstract: Significant reductions in the incidence of enteroviruses and noroviruses, both transmitted primarily by the faecal-oral route, were noted in 2020 compared to the previous decade, in Victoria, Australia. The enterovirus specimen positivity rate was reduced by 84.2% in 2020, while the norovirus outbreak positivity rate declined by 49.0%. The most likely explanation for these reductions is the concurrence of social restrictions, physical distancing, personal hygiene awareness and international and domestic border… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 12 publications
10
45
0
Order By: Relevance
“…The substantial decline of norovirus in 2020 from an historical baseline rate in Pre-COVID-19 was observed, which aligned with results from England, Germany, Australia and the United States [ 13 , [26] , [27] , [28] ]. Our results also extended the available finding by showing that rotavirus A, adenovirus, and DEC were likewise reduced for their activity in 2020.…”
Section: Discussionsupporting
confidence: 74%
“…The substantial decline of norovirus in 2020 from an historical baseline rate in Pre-COVID-19 was observed, which aligned with results from England, Germany, Australia and the United States [ 13 , [26] , [27] , [28] ]. Our results also extended the available finding by showing that rotavirus A, adenovirus, and DEC were likewise reduced for their activity in 2020.…”
Section: Discussionsupporting
confidence: 74%
“…This reduction in ondansetron dispensing may be related to fewer cases of infective gastroenteritis reported in Australia in 2020 compared to preceding years, likely secondary to COVID-19-related social distancing measures. [36] , [37] , [38] …”
Section: Discussionmentioning
confidence: 99%
“…Eigner et al reported a sharp decrease in the proportion of hospitalized patients in Germany positive for norovirus (less than 1.0%) [ 5 ]. Similarly, the number of norovirus associated outbreaks dramatically declined in Australia after the COVID-19 pandemic started in 2020 compared with previous years [ 6 ]. Outbreaks of norovirus in the USA have also been curtailed post COVID-19 as reported by Kraay et al in a nine-state surveillance system [ 7 ] as well as an analysis of pre- and post-COVID-19 outbreaks using data from the CDC NORS [ 8 ].…”
Section: Discussionmentioning
confidence: 99%